The ciliate, Troglodytella abrassarti, contributes to polysaccharide hydrolytic activities in the chimpanzee colon - Profousová, I; Mihaliková, K; Laho, T; Váradyová, Z; Petrželková, K J; Modrý, D; Kišidayová, S (Folia microbiologica, 2011)
Entodiniomorphid ciliates are intestinal protists inhabiting the colons of African great apes. The participation of intestinal entodiniomorphid ciliates in ape hindgut digestion has been proposed, but little data have been available to support the hypothesis. We measured the specific activities of carboxymethyl cellulase, xylanase, inulinase, and α-amylase against different polysaccharides in the feces of captive chimpanzees and evaluated the participation of the entodiniomorphid ciliate, Troglodytella abrassarti, in these activities. T. abrassarti contributed to the total fecal hydrolytic activities of CM-cellulase by 16.2%, α-amylase by 5.95%, and xylanase by 0.66%. Inulinase activity in T. abrassarti samples was not measurable at reaction conditions used. The ciliates, T. abrassarti, actively participate in the chimpanzee hindgut fermentation of fiber and starch.
Keywords: Animals; kolon; polysacharidy; Colon; feces; zvířata; Feces; hydrolýza; Ciliophora; Polysaccharides; Hydrolysis; Pan troglodytes